Examining a Decade of Research in Online Teacher Professional Development - Lay, Celina Dulude; Allman, Bohdana; Cutri, Ramona Maile; Kimmons, Royce (Frontiers in Education, 2020)
This systematic review documents the progress of research in the area of online teacher professional development (oTPD) and seeks to inform developers and facilitators on the complex and unique empirical indicators that are important in designing, developing, implementing, evaluating, and researching oTPD. The 73 studies analyzed in this review suggest that the research in oTPD is progressing toward more rigorous empirical methods and theoretically-grounded design, implementation, and evaluation. Research in oTPD is moving forward in more sophisticated ways and adding to our understanding of high-quality practices that engage teachers in meaningful teacher professional learning in online contexts.